Ethyl Acetate Fraction of Hemerocallis citrina Baroni Decreases Tert-butyl Hydroperoxide-Induced Oxidative Stress Damage in BRL-3A Cells. (8th November 2018) - Wang, Jing; Hu, Dongmei; Hou, Jing; Li, Shushu; Wang, Weiping; Li, Jun; Bai, Jie
Abstract : The main purposes of this study were to screen the antioxidant activities of various fractions of Hemerocallis citrina Baroni and test their hepatoprotective effects in vitro. Antioxidant assays (2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2 ′ -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and reducing power experiments) and tert-butyl hydroperoxide- (t-BHP-) induced BRL-3A oxidative damage experiments were performed in vitro. The H. citrina ethyl acetate fraction (HCEA) was determined to have strong antioxidant activity because of its high flavonoid and polyphenol content. Ultraperformance liquid chromatography- (UPLC-) photodiode array (PDA)/mass spectrometry (MS) analysis showed that the main components of the HCEA were flavonoids and caffeic acid derivatives. A total of 17 compounds were identified. HCEA also effectively protected the liver against t-BHP-induced oxidative stress injury and significantly reduced reactive oxygen (ROS) accumulation. Moreover, HCEA significantly reduced levels of alanine aminotransferase (ALT), aspartate transaminase (AST), and lactate dehydrogenase (LDH). Further studies have shown that HCEA inhibits t-BHP-induced apoptosis by increasing B-cell lymphoma-2 (BCL-2) activity and decreasing caspase-3 and caspase-9 activity. Moreover, HCEA enhanced the activity of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), as well as the total antioxidant capacity (T-AOC), and increased the antioxidant level of glutathione (GSH) in BRL-3A cells. HCEA increased the antioxidant capacity of cells by increasing the gene expression of AMP-activated protein kinase ( AMPK ), extracellular signal-regulated kinase ( ERK ), P38, nuclear factor, erythroid 2 like 2 ( Nrf2 ), SOD, glutamate-cysteine ligase catalytic subunit ( GCLC ), glutamate-cysteine ligase modifier subunit ( GCLM ), and heme oxygenase 1 ( HO-1 ), which are associated with antioxidant pathways to protect against oxidative stress. In conclusion, HCEA protected BRL-3A cells against t-BHP-induced oxidative stress damage via antioxidant and antiapoptosis pathways. Therefore, H. citrina Baroni may serve as a potential hepatoprotective drug.